Once you're choosing, nobody's perfect: is more information necessarily better in oocyte donor selection?. Issue 3 (March 2015) - Rubin, Lisa R.; de Melo-Martin, Inmaculada; Rosenwaks, Zev; Cholst, Ina N.
Abstract Despite a growing body of research examining the psychosocial issues involved in oocyte donation, few studies have examined the role of information in the process of donor selection. The aim of this interview-based qualitative study was to understand how donor oocyte recipients relate to information provided about potential oocyte donors, how they use this information to select donors and their preferences for, and reactions to, various types of information provided to them. Donor oocyte recipients who underwent treatment between 1995 and 2011 were recruited for participation from an academic centre for reproductive medicine. Twenty-two oocyte donor recipients participated. Findings indicate that recipients use information to select donors who they believe would enable them to fulfill their priorities: having a healthy child and 'passing' as genetically related. Obtaining more specific information prompted a focus on donor imperfections and presented a burden of choosing. Moreover, for participants preferring distance, having more information created dilemmas by making the donors less abstract. Although more information and options are often desired by oocyte donor recipients, increased choice can also present psychological dilemmas and emotional costs. Further research is needed to investigate the influence of information-related conflicts on patient decision-making, post-treatment emotional adjustment and disclosure decisions.